Order Interval Secant Method for Nonlinear Systems (Journal of Computational Mathematics, 1985)
An order interval secant method is given. Its rate of convergence is faster than that of order interval Newton method in [1]. The existence and uniqueness of a solution to nonlinear systems and convergence of the interval iterative sequence are also proved.